2014
DOI: 10.1073/pnas.1321776111
|View full text |Cite
|
Sign up to set email alerts
|

Metformin promotes lifespan through mitohormesis via the peroxiredoxin PRDX-2

Abstract: The antiglycemic drug metformin, widely prescribed as first-line treatment of type II diabetes mellitus, has lifespan-extending properties. Precisely how this is achieved remains unclear. Via a quantitative proteomics approach using the model organism Caenorhabditis elegans, we gained molecular understanding of the physiological changes elicited by metformin exposure, including changes in branched-chain amino acid catabolism and cuticle maintenance. We show that metformin extends lifespan through the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
218
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(240 citation statements)
references
References 64 publications
19
218
1
2
Order By: Relevance
“…We have also provided the evidence of H2O2-induced mitohormetic effects in yeast [35]. Just recently, metformin has been proven to promote worm lifespan through mitohormesis via the peroxiredoxin PRD-2 [36]. In the present study, we have also validated that ART, SNP, ARG, or H2O2 can mimic CR to induce SOD, CAT, and GSH for effective ROS scavenging.…”
Section: Discussionsupporting
confidence: 72%
“…We have also provided the evidence of H2O2-induced mitohormetic effects in yeast [35]. Just recently, metformin has been proven to promote worm lifespan through mitohormesis via the peroxiredoxin PRD-2 [36]. In the present study, we have also validated that ART, SNP, ARG, or H2O2 can mimic CR to induce SOD, CAT, and GSH for effective ROS scavenging.…”
Section: Discussionsupporting
confidence: 72%
“…The unresolved question is how metformin activates Nrf2. One possibility is that metformin induces mitohormesis through perturbing the mitochondrion respiratory chain (De Haes et al., 2014; Foretz et al., 2010). However, very high concentrations of metformin (5 m m ) were required to observe significant inhibition of mitochondrion respiratory chain complex 1 activity (He & Wondisford, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effects of metformin on elongating lifespan have been demonstrated in animal models, including worms (Cabreiro et al., 2013; De Haes et al., 2014; Onken & Driscoll, 2010; Wu et al., 2016), mice (Martin‐Montalvo et al., 2013), and rats (Smith et al., 2010). The current consensus is that metformin targets multiple cellular signaling pathways closely associated with the development of aging, such as inflammation, cellular survival, stress defense, autophagy, and protein synthesis (Barzilai et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In line with recent studies proposing a "substrate limitation" model of metformin action, 34,35 we recently revealed that the anti-diabetic/antiaging drug metformin [36][37][38][39] impedes the production of several mitochondrial-dependent biosynthetic intermediates by reducing the anaplerotic flux of glucose, glutamine, and likely branched-chain amino acids, 40 into the tricarboxylic acid (TCA) cycle, leading to the depletion of acetyl-CoA and malonyl-CoA required for de novo lipid biosynthesis and inhibition of mTOR-driven protein synthesis in anabolism-addicted BRCA1 haploinsufficient cells. 41 To mark histones post-translationally, chromatin modifiers use metabolic intermediates such as acetyl-CoA, the key cofactor used by histone acetyltransferases (HATs). Hence, histone modifications may reflect the metabolic status of cells and be influenced by the concentrations of epigenetic metabolites such as acetyl-CoA.…”
mentioning
confidence: 99%